Facets Predicting Quality of Life in Patients with Blood Pressure Disorders - Shafiq, Sameera; Farooq, Aisha; Muhammad, Qurat-ul-Ain (Journal of Liaquat University of Medical & Health Sciences, 2021)
Objective: To explore the predictable relationship of emotional states such as stress and aggression along with coping strategies and quality of life in patients diagnosed with either hypertension or hypotension. Methodology: This Cross-Sectional Correlational study conducted at Department of Psychology, University of Gujrat from December 2019 to July 2020. One hundred eighty patients diagnosed with blood pressure disorders purposively selected from different hospitals in Gujrat and Lalamusa. Urdu versions of Perceived Stress Scale (PSS), Buss and Perry Aggression Questionnaire (BPAQ), Coping Styles Scale (CSS), and a shorter version of World Health Organization Quality of Life (WHOQOL-BREF) used in the study. The Cronbach’s alpha reliability index (?) for these scales is 0.75, 0.83, 0.74, and 0.87 respectively on the present sample. Results: In total of 180 participants, 75% females suffered from blood pressure disorder above age of 30 years (75%), living in rural areas (54%) with primary education (49%). 86% respondents have monthly income less than 50000. 81% patients were married, living in joint family system (51%). There is a significant negative correlation of PSS and BPAQ with WHOQOL. Significant correlation coefficients had been found among perceived stress, aggression, problem solving coping style, emotional coping style and quality of life. Moreover, perceived stress, aggression, and coping strategies significantly predicted quality of life in patients with hyper- and hypotension. Conclusion: The results have posited that quality of life in patients with blood pressure disorders is predictable by perceived stress, aggression, and coping strategies used. Key words: Aggression, Hypertension, Hypotension, Quality of Life.